Assistance for the Registration of Waqf Land Managed by the Leaders of The Muhammadiyah Branch, Kecamatan Dau-Malang - Dwi Ratna Indri Hapsari; Muhammad Luthfi; Yaris Adhial Fajrin (Jurnal Dedikasi Hukum, 2023)
Most of the waqf assets received by PCM DAU from the Wakifs are immovable waqf assets in the form of land. Waqf land managed by PCM DAU is a total of 36 waqf assets, while waqf land that does not yet have a certificate is a total of 10 waqf assets. Obstacles to not registering waqf land are the lack of human resources, lack of awareness about the importance of registering waqf land, a culture of society that has high trust in Nadzir to manage the waqf land, the understanding that waqf is legal and has legal force only by following the provisions in Fiqh Islam, the notion that the management of waqf land certificates is too convoluted, the procedure is long and requires high costs. To solve this problem the service team provides a solution by providing: Socialization regarding the urgency of Waqf Land Registration; Dissemination of waqf land registration procedures starting from the handing over of waqf land by the wakif to the issuance of the waqf land certificate; Assistance in the identification and completion of the documents needed in the registration of waqf land; Assistance in registering waqf land until it enters the National Land Agency (BPN). The mentoring method is used in this service activity with an individual approach. The process for socializing the urgency of waqf land registration will be carried out on March 20, 2021, while the implementation of the socialization of waqf land registration procedures will be carried out on May 15, 2021, for assistance activities for identification and completeness of waqf land registration documents from May 1 to August 23, 2021, as for the process of assisting land registration waqf to the BPN office will be carried out on December 7, 2021.   Abstrak Pendampingan Pendaftaran Tanah Wakaf yang Dikelola Pimpinan Cabang Muhammadiyah Kecamatan Dau-Malang. Harta benda wakaf yang diterima oleh PCM DAU dari para Wakif sebagian besar merupakan harta wakaf tidak bergerak berupa tanah. Tanah wakaf yang dikelola oleh PCM Dau adalah sejumlah 36 aset wakaf, sementara tanah wakaf yang belum memiliki sertifikat adalah sejumlah 10 aset wakaf. Kendala belum dilakukannya pendafatran tanah wakaf adalah kurangnya sumber daya manusia, kurangnya kesadaran tentang pentingnya pendafatran tanah wakaf, kultur masyarakat yang memiliki kepercayaan yang tinggi kepada Nadzir untuk mengelola tanah yang diwakafkan, pemahaman bahwa wakaf telah sah dan memiliki kekuatan hukum hanya dengan mengikuti ketentuan dalam Fiqh Islam, Anggapan bahwa pengurusan sertifikat tanah wakaf terlalu berbelit – belit, prosedurnya lama dan membutuhkan biaya tinggi. Untuk menyelesaikan permasalahan tersebut tim pengabdi memberikan solusi dengan pemberian: Sosialisasi mengenai urgensi Pendaftaan Tanah Wakaf; Sosialisasi mengenai prosedur pendaftaran tanah wakaf mulai dari penyerahan tanah wakaf oleh wakif sampai dengan terbitnya sertifikat tanah wakaf; Pendampingan identifikasi dan kelengkapan dokumen – dokumen yang dibutuhkan dalam pendaftaran tanah wakaf; Pendampingan pendaftaran tanah wakaf sampai masuk ke Badan Pertanahan Nasional (BPN). Metode pendampingan digunakan dalam kegiatan pengabdian ini dengan pendekatan individual. Poses pelaksanaan sosialisasi urgensi pendaftaran tanah wakaf dilakukan pada 20 Maret 2021, sedangkan pelaksanaan sosialisasi prosedur pendaftaran tanah wakaf dilakukan pada 15 Mei 2021, untuk kegiatan pendampingan identifikasi dan kelengkapan dokumen pendaftaran tanah wakaf dilakukan 1 Mei sampai dengan 23 Agustus 2021, adapun proses pendampingan pendaftaran tanah wakaf ke kantor BPN dilaksanakan pada tanggal 7 Desember 2021.